2004
DOI: 10.1097/00006982-200402000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indocyanine Green Injection on the Retinal Surface and Into the Subretinal Space in Rabbits

Abstract: Subretinal delivery of ICG (5 mg/mL) in rabbits induces retinal pigment epithelium, photoreceptor inner and outer segment, and outer nuclear layer damage. These mechanisms of damage may explain the retinal pigment epithelium changes that are sometimes seen after ICG-assisted internal limiting membrane peeling in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 24 publications
2
60
1
4
Order By: Relevance
“…Alterations of the plane of separation between the ILM and the underlying neurosensory retina have also been observed on electron microscopy (14)(15)(16). In vitro and in vivo experimental studies demonstrated direct toxicity of ICG on the pigment epithelium and neurosensory re t i n a (11,(17)(18)(19). These adverse effects were correlated with the sodium concentration in the ICG solvent (20,21), osmolarity (10,22), ICG exposure time (17), and the concentration of the solution (8)(9)(10)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 90%
“…Alterations of the plane of separation between the ILM and the underlying neurosensory retina have also been observed on electron microscopy (14)(15)(16). In vitro and in vivo experimental studies demonstrated direct toxicity of ICG on the pigment epithelium and neurosensory re t i n a (11,(17)(18)(19). These adverse effects were correlated with the sodium concentration in the ICG solvent (20,21), osmolarity (10,22), ICG exposure time (17), and the concentration of the solution (8)(9)(10)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 90%
“…Several reports 49,[62][63][64] evaluated the potential toxicity of ICG, at different concentrations, injected into the subretinal space in animal models. The rational for this approach is to simulate the contact that occurs between ICG and the RPE and photoreceptors when the dye is applied to full-thickness macular holes.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Macular hole (MH) closure rate may be achieved in 74 to 100% of patients using ICG-guided ILM peeling (4,8) . However, the potential for toxic effects of ICG on the re- and hyperfluorescent image at the topography of the previous macular hole position (arrowhead) due to probable window defects related to RPE atrophic changes tina has been suggested (9)(10)(11) . ICG may persist after macular hole surgery for up to 36 months (4) .…”
Section: Indocyanine Greenmentioning
confidence: 99%
“…Most of the studies in this meta-analysis used ICG in high concentrations and volumes. The hypotheses of RPE toxicity to retina is based on 2 different mechanisms: 1) The iodine/singlet oxygen released by the ICG molecule especially if irradiated by light and its metabolic derivates damage the RPE (9)(10)(11) ; 2) The ICG may affect the cleavage plan from the ILM/neurosensory retina resulting in damage to the retina due to removal of Muller and glia cells during the peeling procedure (23) . ICG has been also used to facilitate ILM peeling in other diseases.…”
Section: Indocyanine Greenmentioning
confidence: 99%